The Infographic Video Projects in Japanese Speaking Class - A Arianingsih (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to describe the procedure of implementation of an Infographic Video Project as a learning method in Japanese speaking class and students’ responses to this project. This research used a descriptive method. The sample of this research is 30 students of the 6th semester Japanese Department of UNIKOM in 2020/2021 academic year. The research instrument is a questionnaire. The results show that the student’s response in working on this project was good. Although there are some difficulties encountered in the process, this project has many benefits. The Infographic Video Projects is one method that can be used in Japanese speaking class